Legal Protection for Micro, Small, and Medium Enterprises in the Context of Licensing Legality - Annisa, Jihan; Hanif , Devani Mauriza; Artasena , Iqbal; Sutrisno , Endang; Gunawan , Moh Sigit (Journal of Legal and Cultural Analytics, 2025)
MSMEs play an essential role in the national economy and the regional economy. Legal protection needs to be provided to MSMEs, but MSME actors do not realize or do not understand the importance of licensing as the main requirement for capital and business development. This study aims to determine the extent of legal protection of MSMEs in Kuningan Regency, which is engaged in the culinary industry, because many MSME actors do not understand the importance of business legality. This study uses qualitative methods and normative juridical approaches. It uses laws such as Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Licensing, Kuningan Regency Regional Regulation Number 3 of 2024 concerning the Facilitation, Protection, and Empowerment of Cooperatives and Micro Enterprises, and Kuningan Regent Regulation Number 20 of 2008 concerning Micro, Small, and Medium Enterprises. The study's results show that although the local government has provided various facilities, such as assistance in registering Business Identification Numbers (NIB) and training for micro, small, and medium enterprises (MSMEs), there are still many problems. This study emphasizes that local governments must increase socialization and mentoring so that MSMEs in Kuningan Regency can develop into legal, independent, and competitive businesses.